2022
DOI: 10.3389/fped.2022.888282
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Idiopathic subglottic stenosis in a girl; successful treatment with macrolides

Abstract: An 8-year-old girl presented with treatment-refractory cough and inspiratory stridor. Bronchoscopies showed progressive scarring leading to narrowing of the proximal trachea (Myer-Cotton Grade 2) and epithelial metaplasia of the tracheal and bronchial mucosa. After excluding other causes of congenital and acquired tracheal stenosis, an idiopathic subglottic tracheal stenosis (iSGS) was diagnosed. Because of the patient's young age, a judicious therapeutic approach seemed appropriate. Therapy with azithromycin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…A recent analysis published by Hillel et al identified a specific microbiota of Moraxella (Prevotella and Streptococcus) that occurs significantly more often in patients with ITS compared to control group ( 23 ). A possible effect of a locally altered microbiome and a successful therapy of a idiopathic stenosis with macrolides in an 8-year-old child was reported by Tebbe et al ( 24 ). Those might be additional factors favorizing the development of “idiopathic” tracheal stenosis.…”
Section: Discussionmentioning
confidence: 80%
“…A recent analysis published by Hillel et al identified a specific microbiota of Moraxella (Prevotella and Streptococcus) that occurs significantly more often in patients with ITS compared to control group ( 23 ). A possible effect of a locally altered microbiome and a successful therapy of a idiopathic stenosis with macrolides in an 8-year-old child was reported by Tebbe et al ( 24 ). Those might be additional factors favorizing the development of “idiopathic” tracheal stenosis.…”
Section: Discussionmentioning
confidence: 80%